Protecting Surgical Patient Safety During the Coronavirus Disease 2019 (COVID-19) Pandemic - Enrico M. Forlenza, B.S; Jorge Chahla, M.D., Ph.D; Brian Forsythe, M.D (Elsevier, 2021)
Abstract: As elective surgery slowly reopens across the country, it is paramount that surgeons recognize and take responsibility for their roles in protecting patient safety during the coronavirus disease 2019 pandemic. Namely, these include (1) to prevent further spread of the severe acute respiratory syndrome-CoV-2 virus, (2) to understand the shift in injuries that has occurred as a result of altered lifestyles led by our patients, and (3) to leverage our platforms to disseminate information regarding how individuals can maintain musculoskeletal health during the pandemic. Efforts taken to reduce the spread of severe acute respiratory syndrome-CoV-2 virus can be focused on 3 broad categories of provider-patient interaction: preoperative and clinic visits, surgical encounters, and postoperative care.